NILAI KURS RUPIAH, INFLASI, INDONESIA CRUDE PRICE (ICP) DAN SERTIFIKAT BANK INDONESIA (SBI) IMPLIKASINYA TERHADAP NILAI INDEKS HARGA SAHAM GABUNGAN (IHSG) MENJELANG MEA 2015 - -, Febriyato (Jurnal Manajemen Magister Darmajaya, 2018)
The purpose of this research is to analyze the value of Indonesian Rupiah Exchange Rate, Inflation, Value of Indonesia Crude Price (ICP) and Bank Indonesia Certificates (SBI) implication on Joint Stock Price Index (IHSG) in Indonesia Stock Exchange (IDX) ahead of AEC (Asean Economic Community) 2015. The sample of data used in this study is the JCI, Inflation, ICP, Rupiah Exchange Rate, SBI data on closing each end of the month with observation time of 2014-2015. The selection of 2014-2015 period is to obtain results of data appropriate to the situation at the time of implementation of AEC (Asean Economic Community) 2015. The research method used is quantitative method with multiple regression analysis tool. The use of such analysis to test the magnitude and direction of influence between Exchange Rate, Inflation, ICP and SBI against JCI value. The hypothesis of this research is